Corrosion of inconel alloys for application as inert anodes in low-temperature molten carbonate electrolysis processes. (21st April 2021) - Frangini, S.; Paoletti, C.; Della Seta, L.
Abstract: In this work, five different Inconel alloys were investigated as stable CO2 /O2 evolving anodes for possible use in molten carbonate CO2 and H2 O electrolysis or CO2 /H2 O co-electrolysis processes. Experiments were conducted in the molten ternary Li2 CO3 –Na2 CO3 –K2 CO3 carbonate eutectic at 500 °C, under a CO2 gas atmosphere. Cyclic voltammetry and galvanostatic polarization using DC and pulsed modes of current application were used to evaluate the influence of chemical composition on the Inconel corrosion behavior and anode stability. Results indicated that Ti and Al alloying elements are critical factors in promoting Inconel alloy passivation in molten carbonates, thus allowing high anode stability to be achieved during multiple voltammetric cycles with electrodes made of Inconel 617, 718 and X-750 alloys. It was also found that the mode of current application dramatically affects the galvanostatic polarization results. Although rapid anode degradation was invariably observed in all the Inconel electrodes subjected to DC polarization, electrodes of Inconel 617 and Inconel X-750 alloys were totally immune to anode degradation under pulsed polarization conditions, thus confirming the anode stabilizing effect of (Ti + Al) alloying. The Inconel 617 showed also an excellent gas evolution electrocatalytic activity probably because of its high Co content. Active oxygen formation during anodic gas evolution was a hypothesized mechanism to explain the galvanostatic results. Drastic drop of active oxygen concentration and in particular of the corrosive superoxide ion is supposed to occur on the anode surface during the pulse off-time periods, thus improving Inconel anode stability. Graphical abstract: Image 1 Highlights: Inconel alloys were evaluated as inert anodes for molten carbonate electrolysis. The anodic behavior was studied in the ternary eutectic Li/Na/K mixture at 500 °C. The role of alloy composition to improve anode stability/activity was defined. Formation of corrosive active oxygen to explain anode instability was assumed. Gas evolution conditions for using Inconel as inert anodes were suggested.